2011
DOI: 10.1182/blood-2011-01-330688
|View full text |Cite
|
Sign up to set email alerts
|

The spectrin-based membrane skeleton stabilizes mouse megakaryocyte membrane systems and is essential for proplatelet and platelet formation

Abstract: Megakaryocytes generate platelets by remodeling their cytoplasm first into proplatelets and then into preplatelets, which undergo fission to generate platelets. Although the functions of microtubules and actin during platelet biogenesis have been defined, the role of the spectrin cytoskeleton is unknown. We investigated the function of the spectrin-based membrane skeleton in proplatelet and platelet production in murine megakaryocytes. Electron microscopy revealed that, like circulating platelets, proplatelets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 41 publications
2
59
0
Order By: Relevance
“…27 It has recently been shown that the cortical actin-myosin-spectrin system brings external compressive forces during barbell-shaped proplatelet formation and determines platelet size. 15,19,33 This is important in the context of nonmuscle myosin MYH9-related diseases affecting platelets, 33 and possibly Bernard-Soulier syndrome, and may explain the large size and decreased number of platelets of these patients. Interestingly, membrane skeleton proteins such as b-spectrin and filamin, as well as myosin IIA and moesin, were identified in a screen of proteins able to interact with PI3P.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…27 It has recently been shown that the cortical actin-myosin-spectrin system brings external compressive forces during barbell-shaped proplatelet formation and determines platelet size. 15,19,33 This is important in the context of nonmuscle myosin MYH9-related diseases affecting platelets, 33 and possibly Bernard-Soulier syndrome, and may explain the large size and decreased number of platelets of these patients. Interestingly, membrane skeleton proteins such as b-spectrin and filamin, as well as myosin IIA and moesin, were identified in a screen of proteins able to interact with PI3P.…”
Section: Discussionmentioning
confidence: 99%
“…The spectrin-based membrane skeleton is critical for biophysical membrane properties, both in platelets and megakaryocytes, 27,28 and is essential for the conversion from preplatelets to barbell-shaped proplatelets and to mature platelets. 15,19 The membrane skeleton of WT and PI3K-C2a WT/D1268A platelets was isolated, and its composition analyzed by immunoblotting. Although the level of cortical polymerized actin was normal, a significant decrease of cortical spectrin and myosin was observed in PI3K-C2a WT/D1268A platelets compared with in WT platelets ( Figure 5B).…”
Section: Pi3k-c2amentioning
confidence: 99%
See 1 more Smart Citation
“…5h). We have also recently shown that barbell proPLTs treated with the spectrin disrupting peptide spα2N1 are unable to retain their barbell shape and collapse into a circular prePLT form 14 . These observations confirm that elongating microtubule bundles in the peripheral coil are being deformed by the external compressive pressure of the actin-myosin-spectrin cortex during proPLT conversion.…”
Section: Quantification Of Plt Intermediates In Bloodmentioning
confidence: 94%
“…In this issue of Blood, To-Figueras and colleagues present convincing genetic and biochemical evidence that the clinical phenotype of the rare disorder is markedly affected by the coinheritance of an activating mutation in the erythroid-specific isoform of ␦-aminolevulinic acid synthase. 1 M ost physicians look on the porphyrias with a jaundiced eye. These disorders are rare, the clinical phenotypes are complex and highly variable, the laboratory evaluation is expensive and difficult to access, and the results are usually negative or inconclusive.…”
Section: Uros and Alas-2: Erstwhile Partners In Crime ---------------mentioning
confidence: 99%